OPTIMIZATION OF NURSING MOTHER'S NUTRITION USING SPECIAL MILK FORMULAS - T.E. Borovik; V.A. Skvortsova; G.V. Yatsyk; I.A. Belyaeva; O.L. Lukoyanova; N.N. Semenova; E.О. Terzyan ("Paediatrician" Publishers LLC, 2011)
The article is dedicated to the problem of rational nourishment of nursing mothers. It contains approximate daily set of nutrients and recommended norms of main nutrients and energy intake during lactation. This article also underlines the necessity of enriching women's diet during lactation with essential functional nutritional factors and thus the possibility of use of enriched products for pregnant and nursing women. Also there's information about contents of Russian specialized formula «Annamaria - Prima for nursing mothers», its functional properties, as well as our own clinical observations of mothers, who were receiving this formula. Key words: nursing mother's nourishment, lactation, children. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (5): 111-116.)